2021
DOI: 10.1007/s10461-021-03376-9
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of a Mobile Intervention to Support Mental Health and Adherence Among Adolescents Living with HIV in Western Kenya

Abstract: Mobile technologies represent potentially novel and scalable intervention delivery platforms for adolescents living with HIV (ALWH) in low- and middle-income countries. We conducted a prospective, mixed methods pilot study to evaluate the acceptability and feasibility of the WhatsApp® platform to deliver individual counseling services and facilitate peer support for ALWH in western Kenya. Thirty ALWH (17 female, mean age 15.4) on ART, engaged in HIV care and aware of their status, were enrolled. After 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 67 publications
(75 reference statements)
2
67
0
Order By: Relevance
“…The majority of articled revised were studies conducted in the United States (12) [ 77 , 80 82 , 84 , 88 , 90 , 94 , 95 , 99 , 100 , 104 ], three were from Kenya [ 86 , 92 , 102 ] and three from South Africa [ 85 , 93 , 101 ]. Locations like China, the United Kingdom and Zambia had two studies included in this review [ 79 , 87 , 91 , 96 , 98 , 103 ] and, from the total of articles included, only one article was from Malaysia, Nigeria, Tanzania and Uganda [ 78 , 83 , 89 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of articled revised were studies conducted in the United States (12) [ 77 , 80 82 , 84 , 88 , 90 , 94 , 95 , 99 , 100 , 104 ], three were from Kenya [ 86 , 92 , 102 ] and three from South Africa [ 85 , 93 , 101 ]. Locations like China, the United Kingdom and Zambia had two studies included in this review [ 79 , 87 , 91 , 96 , 98 , 103 ] and, from the total of articles included, only one article was from Malaysia, Nigeria, Tanzania and Uganda [ 78 , 83 , 89 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the study type, eight of the included articles corresponded to pilot studies [ 77 , 79 , 86 , 88 , 92 , 101 , 102 , 104 ], while seven articles explicitly indicate a clinical trial type of design [ 83 , 85 , 86 , 90 , 95 , 96 , 98 ], as well as five protocols [ 80 82 , 93 , 94 ] and five qualitative studies [ 87 , 91 , 99 , 100 , 103 ]. Only two Randomized Controlled Trials [ 78 , 97 ], and one cohort study [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Limited data are available regarding the prevalence of mental health disorders among ALHIV in African countries [22]. A recent pilot study in this population reported depression 3.3% and anxiety 6.7% on baseline assessments [47]. Larger studies among ALHIV in Kenya and other countries in the region have found higher rates of depression (17.8%-25%) and anxiety (32.3%) [50][51][52][53].…”
Section: Plos Onementioning
confidence: 86%
“…Overall proportions of taking a dose >1 hour late in the last 7 days, missing at least 1 dose in the past 7 days, and forgetting to take ART within the last 3 days were 19.5%, 6.3%, and 6.3%, respectively. Studies of adolescent-or caregiver-reported adolescent adherence to ART in this setting have previously noted slightly higher proportions of taking ART >1 hour late in the last 7 days (26-29%); missing at least 1 dose in the past 7 days (16-18%); and forgetting to take ART within the last 3 days (8%) [47][48][49]. It is possible that respondents were less likely to report adherence challenges in phone surveys than in inperson studies.…”
Section: Plos Onementioning
confidence: 96%
“…Nine studies targeted orphans and vulnerable adolescents from poor backgrounds ( 30 , 37 , 41 , 62 ), with one of the studies focusing on AIDS orphaned adolescents ( 30 ). Overall, four interventions were aimed at improving the mental health of HIV-affected adolescents ( 30 , 32 , 40 , 80 ). Ten of the community-based interventions were home-based and involved family meetings involving caregivers, parents, and adolescents.…”
Section: Resultsmentioning
confidence: 99%